Análise de dimensionamento em lajes maciças bidirecionais sobre apoios rígidos e flexíveis - Bezerra, Laercio Cleidson (Universidade Federal Rural do Semi-Árido, 2018)
There are numerous mathematical models for the study of bending behavior of slabs. They are used to analyze internal stresses and displacements, according to the contour conditions, their shape and the loads imposed on the plates. With the expansion of the computational system, more and more developed software such as the Structural Analysis Program (SAP 2000), based on the Finite Element Method (MEF), has been developed, allowing a more precise and global analysis of the structure, such as simulating the constraints in each element coming closer to reality. The simplified model using the Marcus and Bars tables are isolated slabs, disregarding the flexibility of the beams that support it. In order to perform the structural analysis, a model is needed, especially one that is closest to the real structure. For this purpose, the work compares a simple pavement, obtaining its efforts and displacements in several ways, using the simplified method or manual, observing its validation together with the MEF from the SAP 2000. Otherwise, in a bolder pavement, the internal stresses and arrows were analyzed, from the manual method, noting that depending on the shape of the pavement under study, the simplification may render the method impractical when comparing the structure outlined for MEF in SAP 2000.
Monografia
Keywords: Modelo simplificado; Flecha; Análise estrutural; Simplified model; Arrow; Structural analysis; ENGENHARIAS::ENGENHARIA CIVIL